F-1 Visa - Anand, Saurabh (Journal of International Students, 2021)
Listen to the poem read by Saurabh Anand (author) with audio production by Ron Braxley:Check if it's OK with your visa and all?Writing Op-Eds on such things can be tricky.F-1 is like being behind the eight-ball.You’re not American, so why do their politics bother y’all?You’re here to study, yet locals may still go freaky.Check twice before you cause trouble with your visa and all.You don't even have a hyphenated identity. It's not your call,Don't ruin what you have. This path will not be easy.The F-1 visa keeps one behind the eight-ball.India and the U.S. are allies. Your decisions will declare you: mole.You’re a taxpayer but a stepchild in this country’s family,so check the consul’s small print on your visa and all.What if you get your dream job in this country after you graduate next Fall?You might afford a home, sponsor your parents, and live here freely,Don't take a chance at all. Being on F-1 is like being behind the eight-ball.I know how badly we both wanted to go to the #BLM protest at City Hall,But what if we get caught and need an attorney?Let’s check first. Would we be okay with the visa and all? Remember, we could loseour status, in an instant, since F-1s, at risk of being sunk,are forever behind the eight-ball.